(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
It is known that the formation of the content of life values in teenagers is greatly influenced by the social environment that surrounds them and is important for them. Analyzing the social essence of youth subcultures, the content of the structure of leading values in it, plays an important role in providing appropriate psychological-pedagogical influence on the growing generation, and in carrying out preventive work in this regard.